Komunitas Online : Pergeseran Terminologi Komunitas Dari Geddesian Menuju Era Informasi Dalam Konteks Perencanaan Transportasi Perkotaan - Yudi Basuki; Roos Akbar; P Pradono; Miming Miharja (Diponegoro University, 2013)
The purpose of this article is to explain the shift of idea in the notion of Folk to Online Communities. The methodology used is a literature review to establish the conceptual framework.There are two shift ideas, the first is the idea of Geddes, while the online community committed human activity not only in real space but also the virtual space that paved the conception of the unity of geography. The second is that the activity system concept was initiated Manheim no longer just the activities carried out in real space but also the activity is conducted in a virtual space. Concept of trip generation no longer refers to the location of the gathering of traveling performers in a particular geographic area unit. Conception of trip attraction was also no longer always refers to the city center or the center of town services but depends on the deal online community members in conducting physical meetings.